1993
DOI: 10.1038/eye.1993.177
|View full text |Cite
|
Sign up to set email alerts
|

The role of nasolacrimal intubation in the management of childhood epiphora

Abstract: Nasolacrimal intubation has been advocated to obviate the need for dacryocystorhinostomy (DCR) for childhood epiphora which fails to resolve despite apparently successful probings. Twenty-eight intubations were attempted on children falling into this category. Of these, 25 were anatomically successful intubations (3 having had to be abandoned because of difficulties in retrieving the silicone tubes from the nose). Twenty patients (80%) had complete resolution of symptoms, 2 (8%) had improvement of symptoms suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 10 publications
0
27
0
1
Order By: Relevance
“…In congenital nasolacrimal duct obstruction, the duration the silicone stent remains in the passage varies between 6 weeks and 6 months in the published reports [2,4,7,8,19]. In our study, because the average age was relatively high, we planned to leave the tube in for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…In congenital nasolacrimal duct obstruction, the duration the silicone stent remains in the passage varies between 6 weeks and 6 months in the published reports [2,4,7,8,19]. In our study, because the average age was relatively high, we planned to leave the tube in for 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11] On the other hand, the studies including children older than 7 years are very rare, and those studies had study population with wide age ranges also including younger children. 12,13 To the best of our knowledge, there is no study evaluating the success rates of nasolacrimal duct intubation for the treatment of CNLDO in only children older than 7 years of age. Therefore, in the current study, we aimed to investigate the outcomes of primary nasolacrimal duct intubation in the treatment of CNLDO in children older than 7 years.…”
Section: Introductionmentioning
confidence: 99%
“…The question of the optimum duration for the tubes remaining in situ needs an answer. Aggarwal et al [30] recommended that the tubes remain in place for 6 months. However, Marr et al [27] have suggested that this was unnecessarily long and their practice was to remove the tubes after 6 weeks.…”
Section: Discussionmentioning
confidence: 99%